1997
DOI: 10.1152/jn.1997.78.2.767
|View full text |Cite
|
Sign up to set email alerts
|

Response Properties of Neurons in the Inferior Colliculus of the Monaurally Deafened Ferret to Acoustic Stimulation of the Intact Ear

Abstract: Response properties of neurons in the central nucleus of the inferior colliculus (ICC) were investigated after unilateral cochlear removal at various ages during infancy. Nineteen ferrets had the right cochlea surgically ablated, either in adulthood or on postnatal day (P) 5, 25, or 40, 3-18 mo before recording. Adult ablations were made on the same day as ("acute," n = 3), or 2-3 mo before ("chronic," n = 3), recording. Two ferrets were left binaurally intact. Single-unit (n = 702) and multiunit (n = 1,819) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 50 publications
5
76
0
1
Order By: Relevance
“…However, Tucci et al (1999) also measured 2-DG uptake in animals 2 days following ear manipulation, and found the percent difference from SH was on the order of 50 -60%, suggesting that for CHL (and CA) there may be some recovery of activity between 2 days and three weeks. Following unilateral CA, electrophysiological evidence suggests the proportion of units in the opposite IC excited by stimulation of the ipsilateral (intact) ear increases dramatically over time (e.g., McAlpine et al, 1997;Irvine et al, 2003). The mechanism for this change in response characteristics appears to be a rapid reduction in functional inhibition from lemniscal inputs or within the IC itself (e.g., Mossop, et al, 2000;Vale et al, 2004).…”
Section: Sub-cortical Effects Of Unilateral Hearing Lossmentioning
confidence: 99%
“…However, Tucci et al (1999) also measured 2-DG uptake in animals 2 days following ear manipulation, and found the percent difference from SH was on the order of 50 -60%, suggesting that for CHL (and CA) there may be some recovery of activity between 2 days and three weeks. Following unilateral CA, electrophysiological evidence suggests the proportion of units in the opposite IC excited by stimulation of the ipsilateral (intact) ear increases dramatically over time (e.g., McAlpine et al, 1997;Irvine et al, 2003). The mechanism for this change in response characteristics appears to be a rapid reduction in functional inhibition from lemniscal inputs or within the IC itself (e.g., Mossop, et al, 2000;Vale et al, 2004).…”
Section: Sub-cortical Effects Of Unilateral Hearing Lossmentioning
confidence: 99%
“…Evidence from animals with experimentally induced UD indicates that increased neural responsiveness to stimulation of the intact ear occurs over a wide time frame. Initial increases in excitatory responses of cortical and sub-cortical neurons have been demonstrated within minutes to hours post-UD (Popelar et al 1994;Mossop et al 2000), while further changes have been observed a number of months post-UD (McAlpine et al 1997). Therefore, the data from animal studies are consistent with a cascade of multiple processes driving plasticity.…”
Section: Introductionmentioning
confidence: 92%
“…Experimentally induced UD in adult animals leads to increased neural responsiveness to stimulation of the intact ear (Popelar et al 1994;McAlpine et al 1997;Mossop et al 2000). The changes are greatest in the pathway ipsilateral to the intact ear, probably because this pathway normally receives the strongest input from the deafferented ear (Adams 1979;Coleman and Clerici 1987).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations